Person of a criminal who commits bribery in the activities of legal entities under private law - Chehunov , Mykola (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
The article is devoted to a comprehensive criminological analysis of the personality of a criminal who commits bribery in the activities of legal entities under private law. To study the personality of a criminal who commits bribery in the activities of legal entities under private law, comparative legal, formal legal, logical legal, comparative, structural-functional and hermeneutic methods of cognition of social and legal phenomena were used.To achieve the specified goal, a selective study of the materials of criminal proceedings under Articles 354 and 368-3 of the Criminal Code of Ukraine and statistical data presented in the reports of the State Judicial Administration of Ukraine «On the composition of convicts» was conducted.It was found that the multidimensionality of the concept of «personality of a criminal» emphasizes the importance of a comprehensive analysis of its typical properties for criminological science at different levels depending on the purpose of the study.The structure of the personality of a criminal who commits bribery in the activities of legal entities under private law has been analyzed, taking into account socio-demographic, moral-psychological characteristics and signs that determine criminal behavior.It has been concluded that persons who commit bribery in the activities of legal entities under private law are mainly middle-aged and mature men with higher education. They hold managerial or financially responsible positions, endowed with organizational, managerial and administrative and economic powers. The psychological characteristics of such criminals include a deep deformation of legal consciousness and a persistent selfish orientation of criminal behavior. Signs that characterize criminal behavior, or criminal law aspects, indicate that these crimes are usually committed in office offices during working hours by directly transferring an unlawful benefit to the addressee or a third party, the main type of objects of unlawful benefit are money and other property.